Assess the level of occupational stress and to evaluate the effectiveness of planned teaching programme on knowledge regarding occupational stress and its management among security guards of a selected organization, Shimoga, Karnataka - M, Siddesh; H.N, Ravindra. (International Journal of Psychosocial Rehabilitation, 2020)
Occupational stress occurs when there is a disequilibrium between job demands and capabilities. Being employed as a security guard exposes the subject to potentially dangerous situations. Security guards are engaged in a profession that confronts violators of the law as well as violence and are thus are more likely to be exposed to traumatic experiences. So it is very important to assess the level of s tress they possess and make them aware of the harmful effects and how to manage it. Hence, there is a need to assess the level of occupational stress and to evaluate the effectiveness of PTP on knowledge regarding occupational stress and its management among security guards of a selected organization, Shimoga. Karnataka. Results: demonstrated that majority of the security guards were having moderate level of occupational stress. Among 80 security guards 59 (74%) were having moderate level of occupational stress, 21(26%) were having severe level of occupational stress . and none of them possessed mild level of occupational stress. This study contributes to the emerging body of knowledge about occupational stress in their security profession and it is important to plan the healthy coping strategies to cope up with their occupational stress.